2015
DOI: 10.1039/c4cp05727a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast hydrogen bond dynamics and partial electron transfer after photoexcitation of diethyl ester of 7-(diethylamino)-coumarin-3-phosphonic acid and its benzoxaphosphorin analog

Abstract: The solvation dynamics after optical excitation of two phosphono-substituted coumarin derivatives dissolved in various solutions are studied by fluorescence up-conversion spectroscopy and quantum chemical simulations. The Kamlet-Taft analysis of the conventional absorption and emission spectra suggests weakening of the solvent-solute H-bonds upon optical excitation, which is in contrast to the results gained by the quantum simulations and earlier studies reported for coumarin derivatives without phosphono grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Recent studies on p-conjugated systems reported a correlation between uorescence QY and extension in the conjugated p-system. 47,48 Moreover, intramolecular chargetransfer processes, which are common in coumarins, 22,49,50 lead to large changes in dipole moment between ground and excited state accompanied by a signicant increase of the uorescence intensity. 47,50 Accordingly, the rise of Dm from 2.0 D to 4.12 D and 4.65 D going form 6-H to 6-Cl and 6-Br, respectively, suggests an increase of the uorescence QY in the same way.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies on p-conjugated systems reported a correlation between uorescence QY and extension in the conjugated p-system. 47,48 Moreover, intramolecular chargetransfer processes, which are common in coumarins, 22,49,50 lead to large changes in dipole moment between ground and excited state accompanied by a signicant increase of the uorescence intensity. 47,50 Accordingly, the rise of Dm from 2.0 D to 4.12 D and 4.65 D going form 6-H to 6-Cl and 6-Br, respectively, suggests an increase of the uorescence QY in the same way.…”
Section: Resultsmentioning
confidence: 99%
“…20,21 In other approaches the comparably small coumarin moiety was used to study the attached functional groups. [22][23][24] In our case the 3-substituted diethylphosphono and phosphono groups are commonly known for their enzyme inhibiting abilities. 25,26 The electron withdrawing effect of the diethylphosphono group on the conjugated aromatic coumarin structure reduces the electron density stronger on 7 with respect to 6-position.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The absorption and emission spectra of several compounds ( CM-1—CM-12 , Table 1 ), varying the substituent in position C-6 of the coumarin ring were calculated. Based on previous investigations in our group, coumarins bearing substituents in position C-6 [ 33 ] and C-7 [ 34 ] exhibit good fluorescent properties. The model compounds phenyl and aryl groups were chosen to enlarge the conjugated system, connected to the coumarin fragment.…”
Section: Resultsmentioning
confidence: 99%